PERBAIKAN KEKUATAN DAN DAKTILITAS KOLOM BETON BERTULANG YANG MENDAPAT BEBAN GEMPA MENGGUNAKAN GLASS FIBER REINFORCED POLYMER - Parmo Parmo; Agoes Soehardjono M.D.; Tavio Tavio (Teknologi dan Kejuruan, 2014)
Repairing the Strength and Ductility of Reinforced Concrete Column That Got Earthquake using Glass Fiber Reinforced Polymer. This study aims to identify the additional strength and ductility of reinforced concrete columns after being retrofitted using glass fiber reinforced polymer (GFRP) and got the brunt of the earthquake. This study uses two objects tested columns, which are being tested for three times. Each column size is 350 x 350 x 1100 mm with f'c = 20.34 MPa and fy = 549.94 MPa. The testing is performed by giving a constant axial load of 748 kN and cyclic lateral load using control displacement method in order to simulate the brunt of earthquake. The results show an increase in lateral capacity of column by 43.96%. Retrofitting the column with GFRP has a ductile property, which is shown by the increase of the displacement ductility by 129.14% and curvature ductility by 118.27%.